Optical properties of stanene. (8th November 2016) - Chaudhary, Raghvendra Pratap; Saxena, Sumit; Shukla, Shobha
Abstract: Successful synthesis of graphene has created a runaway effect in the exploration of other similar two-dimensional materials. These materials are important as they provide large surface areas and have led to the exploration of new physical phenomena. Even though graphene has exotic electronic properties, its spin–orbit coupling is very weak. Tin, being one of the heaviest elements in this group, is expected to have enhanced spin–orbit coupling in addition to other exotic properties of graphene. Here we report optical signatures of free standing stanene obtained using UV–vis absorption spectroscopy. Raman measurements were performed on a transmission electron microscope (TEM) grid. Interlayer spacing, phonon frequencies and the imaginary part of the complex dielectric function obtained using first principles methods are in good agreement with the experimental data. Occurrence of parallel bands suggests the possibility of the presence of excitonic effects in stanene.